2015
DOI: 10.7717/peerj.1001
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal modelling of an ostrich (Struthio camelus) pelvic limb: influence of limb orientation on muscular capacity during locomotion

Abstract: We developed a three-dimensional, biomechanical computer model of the 36 major pelvic limb muscle groups in an ostrich (Struthio camelus) to investigate muscle function in this, the largest of extant birds and model organism for many studies of locomotor mechanics, body size, anatomy and evolution. Combined with experimental data, we use this model to test two main hypotheses. We first query whether ostriches use limb orientations (joint angles) that optimize the moment-generating capacities of their muscles d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
194
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(204 citation statements)
references
References 120 publications
(386 reference statements)
10
194
0
Order By: Relevance
“…A modified ex vivo experiment, recording tendon tensions from the patellar complex of an instrumented Numida cadaver(s) subjected to dynamic extensor forces estimated from in vivo data, would perhaps represent the best of both methods, or at least a useful test of the methods and data presented here. However, estimation of the individual muscle forces needed for such an experiment requires a musculoskeletal simulation based on complete skeletal kinematics, limb endpoint forces, segment inertial properties and detailed muscle–tendon unit properties (see Hutchinson et al ., 2015 for an equivalent model of an ostrich). As such, it is beyond the scope of this project, but is a promising line of enquiry for future work.…”
Section: Discussionmentioning
confidence: 99%
“…A modified ex vivo experiment, recording tendon tensions from the patellar complex of an instrumented Numida cadaver(s) subjected to dynamic extensor forces estimated from in vivo data, would perhaps represent the best of both methods, or at least a useful test of the methods and data presented here. However, estimation of the individual muscle forces needed for such an experiment requires a musculoskeletal simulation based on complete skeletal kinematics, limb endpoint forces, segment inertial properties and detailed muscle–tendon unit properties (see Hutchinson et al ., 2015 for an equivalent model of an ostrich). As such, it is beyond the scope of this project, but is a promising line of enquiry for future work.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hill-type models have been used, together with reconstructions of musculoskeletal geometry, to analyse the moment-generating capacities of animals during terrestrial locomotion (O'Neill et al, 2013;Hutchinson et al, 2015) and to estimate the locomotor capabilities of extinct species based on fossil records (Hutchinson and Garcia, 2002). Muscle models have also been used in simulations of human locomotion to infer the functions of individual muscles during walking and running (Hamner et al, 2010) and to uncover important insights into the biomechanical factors that contribute to gait abnormalities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their stance phase activity pattern, muscles such as the iliotrochantericus caudalis and medius appear to be ideally situated to induce internal hip LAR (Gatesy, 1994(Gatesy, , 1999b). Yet, Hutchinson et al (2015) found that several of the most significant hip extensors have large internal rotation (called medial rotation in their paper) moment arms at relevant joint angles as well. Determining how these muscles (and active antagonists) interact with inertial loads and passive forces to modulate LAR during stance will require a more sophisticated, fully 3D approach.…”
Section: Implications and Future Workmentioning
confidence: 99%